Gene therapies for RyR1-related myopathies. (February 2023) - Marty, Isabelle; Beaufils, Mathilde; Fauré, Julien; Rendu, John
Abstract: Myopathies related to variations in the RYR1 gene are genetic diseases for which the therapeutic options are sparse, in part because of the very large size of the gene and protein, and of the distribution of variations all along the sequence. Taking advantage of the progress made in the gene therapy field, different approaches can be applied to the different genetic variations, either at the mRNA level or directly at the DNA level, specifically with the new gene editing tools. Some of those have already been tested in cellulo and/or in vivo, and for the development of the most innovative gene editing technology, inspiration can be sought in other genetic diseases.